Text, role, and context developing academic literacies - Johns, Ann M. (Cambridge applied linguistics series, 1997)
"his text explores fundamental issues relating to student literacies and instructor roles and practices within academic contexts.It offers a brief history of literacy theories and argues for "socioliterate" approaches to teaching and learning in which texts are viewed as primarily socially constructed. Central to socioliteracy, the concepts "genre" and "discourse community," are presented in detail. The author argues for roles for literacy practitioners in which they and their students conduct research and are involved in joint pedagogical endeavors. The final chapters are devoted to outlining how the views presented can be applied to a variety of classroom texts. Core curricular design principles are outlined, and three types of portfolio-based academic literacy classrooms are described" -- Provided by publisher.